The relationship between capital structure and performance of Islamic banks - Tarek Al-Kayed, Lama; Syed Mohd Zain, Sharifah Raihan; Duasa, Jarita (Emerald Group Publishing Limited, 2014)
Purpose – This paper aims to examine the effect of capital structure on Islamic banks’ (IBs) performance to provide guidance to finance managers for raising capital funds. As newcomers to the markets, IBs are facing a trade-off. They can either use high capital ratios which increase the soundness and safety of the bank and lower the required return by investors, or depend on deposits and Islamic bonds which are considered cheaper sources of funds due to their tax rebate. An IB’s management must carefully decide the appropriate mix of debt and equity, i.e. capital structure, to maximize the value of the bank. Design/methodology/approach – Using a sample of 85 IBs covering banking systems in 19 countries, the study uses a two-stage least squares method to examine the performance determinants of IBs to control the reverse causality from performance to capital structure. Findings – After control of the macroeconomic environment, financial market structure and taxation, results indicate that IBs’ performance (profitability) responds positively to an increase in equity (capital ratio). The result is consistent with the signaling theory which predicts that banks expected to have better performance credibly transmit this information through higher capital. Optimal capital structure results of the IBs found a non-monotonic U-shaped relationship between the capital-asset ratio and profitability, supporting the efficiency risk and franchise value hypotheses. Research limitations/implications – Due to limitations for market data, the study uses book accounting ratios. Future research where market data are available could use performance measures, such as Tobin’s Q in performance determinants models. Practical implications – The non-monotonic relationship found between IBs’ return on equity and capital ratios suggests that equity issuances for IBs’ with low capital ratios (lower than the turning point of 37.41 per cent) are expensive and have a negative effect on their profitability. On the other hand, managers of well-capitalized IBs (banks with capital ratios beyond 37.41 per cent) are advised to rely on equity when faced by a decision to raise capital, as the capital ratio starts to affect their profitability positively. Originality/value – Islamic banking literature has been silent on IBs’ capital structure and its relevance; this study will try to fill in the existent gap. Keywords Performance, Capital structure, Islamic banks, Optimal capital structure